2021
DOI: 10.1108/bfj-09-2020-0876
|View full text |Cite
|
Sign up to set email alerts
|

Farmer preferences regarding durum wheat contracts in Italy: a discrete choice experiment

Abstract: PurposeThis study aims to investigate farmer preferences regarding sales contracts for durum wheat in Italy.Design/methodology/approachThe authors consider that contracts are formed by an organisational entity that is in charge of transferring decision and property rights based on reductions in transaction costs. The empirical analysis presents a discrete choice experiment with three distinct models that was performed by a survey of 160 wheat farmers in southern Italy.FindingsThe results show that contractual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…However, evidences contrast with Wang et al (2011) and Abebe et al (2013) who reported smallholders' preference for a floating price, when the ex post spot market price is expected to exceed the price proposed in the contract. Oliveira et al (2021) also found a similar pattern in a previous study in the durum wheat sector, where producers were not significantly interested to contractual terms establishing the modality of payment in advance.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…However, evidences contrast with Wang et al (2011) and Abebe et al (2013) who reported smallholders' preference for a floating price, when the ex post spot market price is expected to exceed the price proposed in the contract. Oliveira et al (2021) also found a similar pattern in a previous study in the durum wheat sector, where producers were not significantly interested to contractual terms establishing the modality of payment in advance.…”
Section: Discussionsupporting
confidence: 86%
“…All these clauses refer to quality requirements, which have a large impact on farmers' acceptance because they not only define minimum quality levels but also payment of premium prices. In our case, the reluctance to accept costly obligations, such as an excessive quality threshold (e.g., 14% or even 13% of protein content for durum wheat), can be attributed to possible quality measurement problems in line with Abebe et al (2013) and Oliveira et al (2021).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Discrete choice experiments (DCEs) are suitable methods to elicit preferences for product characteristics when a product is new or not yet commercially available [13]. DCEs are gaining interest in agricultural research and have been used recently, for example, to study preferences regarding interactions with markets with focus on certification or contracts [14][15][16] or preferences for crop characteristics [17][18][19] or farming practices such as the use of inputs such as fertilisers, pesticides, or the application of conservation measures [20][21][22][23][24] and also to investigate preferences regarding agricultural or environmental policies [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%